Freud's Psychoanalytic Personality Structure in the Film Perayaan Mati Rasa and Its Implications as Teaching Material for Junior High School - Febriani Ahmad; Yulianeta; Welsi Damayanti (Jurnal Pembelajaran Bahasa dan Sastra, 2026)
This study aims to describe the personality structure of characters in Umay Shahab’s film Perayaan Mati Rasa based on Sigmund Freud’s psychoanalysis and its implications as literature teaching materials in junior high school. Data were collected through library-based research, with the film serving as the primary data source. The study employed a qualitative descriptive method and a literary psychology approach. The data consisted of dialogues, actions, expressions, and sequences of scenes that demonstrate the operation of the id, ego, and superego in Ian and Uta. Data were collected through repeated viewing, note-taking, and scene-time documentation. The data were analyzed by identifying conflict contexts, classifying evidence into the id, ego, and superego, interpreting the relationships among the three structures, and linking the findings to Phase D literature learning needs. The findings show that the id dominates the early to middle parts of the story through anger, the need for recognition, and resistance to painful situations; the ego works through reality consideration, problem solving, and decision making; while the superego becomes stronger through responsibility, honesty, guilt, and moral integrity. The novelty lies in analyzing all three structures as equally important and dynamically interacting categories rather than focusing only on the dominance of the id, and in translating the findings into scene- and dialogue-based teaching materials that develop students’ viewing, argumentation, empathy, and reflection skills.